1979
DOI: 10.3109/00365527909179870
|View full text |Cite
|
Sign up to set email alerts
|

Intestino-gastric Reflux in Dogs: Spontaneous, after Gastrojejunostomy, and after Roux-en-Y Gastrojejunostomy with Various Lengths of the Defunctioning Loop

Abstract: Intestino-gastric reflux was measured in dogs with duodenostomy and gastrostomy by using chromium-51 injected through the duodenostomy. No transpyloric reflux was demonstrated. When gastrojejunostomy was performed, a large reflux was demonstrated. After conversion of the gastrojejunostomy into a Roux-en-Y gastrojejunostomy with various lengths of the defunctioning loop, a decrease in reflux was demonstrated, significantly correlated to the length of the loop. The calculated length corresponding to no reflux wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Mean operating time was 140 min — compared to 81.5 min in the open procedure. In our study, we reconnected the proximal jejunum approximately 40 cm distal to the stapling line, in accordance with prior studies that demonstrated reflux up to 35 cm . Gallbladder removal was included to provide a setup for possible future robotic‐assisted radical surgery for tumors of the CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Mean operating time was 140 min — compared to 81.5 min in the open procedure. In our study, we reconnected the proximal jejunum approximately 40 cm distal to the stapling line, in accordance with prior studies that demonstrated reflux up to 35 cm . Gallbladder removal was included to provide a setup for possible future robotic‐assisted radical surgery for tumors of the CBD.…”
Section: Discussionmentioning
confidence: 99%